Flat epithelial atypia of the breast on core needle biopsy: an indication for surgical excision. - Sohn V; Porta R; Brown T; Sohn, Vance; Porta, Rees; Brown, Tommy (Military Medicine, 2011)
Objectives: Flat epithelial atypia (FEA) is an increasingly diagnosed breast lesion yet there remains a paucity of data regarding these findings and their clinical significance. By determining the pathologic concordance rate, we sought to evaluate the indications for surgical intervention for FEAs diagnosed on core needle biopsy (CNB).Methods: Using a retrospective review of an international pathology referral center database, we included all breast CNB specimens with FEA as the most advanced diagnosis that underwent surgical excision. Patient demographics, caliber of biopsy needle, and pathology results were then analyzed.Results: Between 2000 and 2009, 463 FEAs were diagnosed among 15,000 specimens referred for expert opinion. Twenty-four lesions (5%) met inclusion criteria. Sampling ranged from 8- to 18-guage needles. Two lesions (8.4%) were upgraded after surgical excision; one patient was found to have infiltrating ductal carcinoma and another with tubular carcinoma. Twelve patients who were diagnosed with FEA did not undergo surgical excision but had no immediate evidence of malignancy.Conclusions: Based on the 8.4% upgrade rate, FEA diagnosed on CNB requires follow-up surgical excision. Regardless of CNB caliber, the risk of sampling error precludes nonoperative management and FEA should be considered an at-risk lesion until more studies and pooled analysis prove otherwise.